A Synthetically Generated LFe(IV)OH(n) Complex - Weitz, Andrew C. (Inorg Chem, 2019)
High-valent Fe–OH species are important intermediates in hydroxylation chemistry. Such complexes have been implicated in mechanisms of oxygen-activating enzymes and have thus far been observed in Compound II of sulfur-ligated heme enzymes like cytochrome P450. Attempts to synthetically model such species have thus far seen relatively little success. Here, the first synthetic Fe(IV)OH(n) complex has been generated and spectroscopically characterized as either [LFe(IV)OH](−) or [LFe(IV)OH(2)](0), where H(4)L = Me(4)C(2)(NHCOCMe(2)NHCO)(2)CMe(2) is a variant of a tetra-amido macrocyclic ligand (TAML). The steric bulk provided by the replacement of the aryl group with the −CMe(2)CMe(2)− unit in this TAML variant prevents dimerization in all oxidation states over a wide pH range, thus allowing the generation of Fe(IV)OH(n) in near quantitative yield from oxidation of the [LFe(III)OH(2)](−) precursor.